Gender, Class and Biography: Theory, Research and Practice - Merrill, Barbara (INSTED: Interdisciplinary Studies in Education & Society, 2011)
This paper is about the lives of some working class women and men who chose to return to learn, as adults, in further and higher education in the UK (I need to explain that further education colleges are post-compulsory institutions which deliver academic and vocational courses). Although the focus is on research undertaken in the UK I hope that the voices, experiences, struggles and achievements of the participants in this paper will have resonance and relevance for you here in Poland. The stories are drawn from several research projects which looked at the access, learning experiences and learning identities of working class adults in educational environments which, particularly in the case of higher education, may seem daunting culturally ? a different community to the communities where they live and have known. How are these differences resolved? How do they cope in these two contrasting spaces and keep on going on? What impact does learning have on their classed and gendered, and for some, raced identities and communities? These issues are discussed within the context of the UK?s lifelong learning policy.